Russian views of the transition in the rural sector : structures, policy outcomes, and adaptive responses - Norsworthy, L. Alexander; World Bank. (Washington, D.C. : International Bank for Reconstruction and Development / World Bank, 2000)
A decade into the reform, the number of collective farms has not changed. These enterprises remain the dominant agricultural producers, while the role of individual farms is still marginal and stagnant (Goskomstat 1997: 38; 1998)."Western strategies are not working for Russian agriculture. To determine why the reforms suggested by Western experts for Russian reformers are either faltering or ignored, the World Bank invited several Russian scholars to submit papers on a variety of rural and social development themes. The scholars' contributions varied from national to local in scope and used rural economic, sociological, political, and demographic analysis to reach their conclusions. Some of their observations were consistent with those of World Bank experts; others, surprisingly, differ substantially from Bank findings. Although the World Bank perspective has been published elsewhere and circulated widely, this volume benefits from the unique perspective of these Russian academicians. In publishing these papers, the editor hopes to stimulate dialogue to assist the Bank in addressing the pressing issues facing rural communities in Russia.
Includes bibliographical references.
aia 19/8/16
Loans
Keywords: Agriculture and state- Russia (Federation).; Russia (Federation)- Rural conditions; Russia